The value of the optic nerve sheath diameter measured using computerized brain tomography in the evaluation of mortality status in patients admitted to the emergency department with intracranial hemorrhage : Optic nerve sheath diameter in relation to intracranial hemorrhage - Boran, Nukhet Burçem; Karakaya, Zeynep; Acar, Hüseyin; Efgan, Mehmet Göktuğ; Bilgin, Serkan (Journal of Surgery and Medicine, 2022)
Background/Aim: The optic nerve sheath diameter (ONSD) measurement is a non-invasive method that can be obtained from computerized tomography (CT) images. It can therefore be a useful diagnostic tool in determining prognosis in the emergency department. The aim of this study was to investigate the relationship between ONSD and mortality status in patients with intracranial hemorrhage who presented to the emergency department by measuring ONSD on computerized brain tomography images taken during admission. Methods: This retrospective cohort study was carried out in the emergency department of a tertiary hospital between December 1, 2018 and December 1, 2020 and included intracranial hemorrhage patients and patients with normal brain CT scans that had been obtained for any reason. Bilateral ONSDs were measured in both the intracranial hemorrhage and control groups. We first evaluated whether ONSD would differ between the two groups after which the relationship between ONSD and mortality was analyzed in the patient group who presented with bleeding. Results: Intracranial hemorrhage was present in half the cases and midline shift in 21.5%. A statistically significant increase in ONSD was observed in cases with intracranial hemorrhage (P < 0.001). Similarly, a statistically significant increase in ONSD was found in cases with midline shifts and mortality (P < 0.001). A cut-off value of 4.19 mm for mean optic nerve diameter exhibited 100% sensitivity and 70% specificity in terms of hemorrhage detection (area under the curve [AUC]: 0.952; P < 0.001). A cut-off value of 6.03 mm for ONSD exhibited 76% sensitivity and 74% specificity in terms of hemorrhage detection (AUC: 0.730; P = 0.001). The odds ratio for prediction of mortality based on a regression analysis was 8.838 in cases with intracranial hemorrhage (P < 0.001). Conclusion: ONSSD measured on CT images is a promising tool for prediction of intracranial hemorrhage, midline shift, and mortality status.